The Effect of Architectural Forms on Aesthetic Response : Study Case - Othman, Lawand Kamal; Ali, Alan Faraydoon (Kurdistan Journal of Applied Research, 2021)
This research seeks to identify building exterior characteristics that are best liked, most pleasing, rated beautiful and exciting by architects. A methodology based on mixed research methods was developed. The study sought architect’s preferences for twelve different public buildings. Analysis of 68 responses to the survey questionnaire identified several building’s exteriors characteristics that were consistently most preferred aesthetically. Four formal attributes. Complexity, Order, Ambiguity, and Potency, each of which was measured by three variables, and one variable added to the ambiguity, so a total of 13 formal (cognitive / perceptual) variables were included in the study. The effects of these attributes on affective responses, i.e., Arousal and Evaluation, each of which was measured by three variables, were examined. The analysis of the scatter chart identifies the level of association between two dependent variables, aesthetic response and formal features. A medium to a strong relationship has been recognized between aesthetic response with moderate complexity and moderate to high levels of order and organization also with near high levels of novelty and mystery. Though, a weak correlation between the remaining of the dependent variables indicates a thin relationship. The higher the level of ambiguity in the exterior, the more excited the receiver. The higher the classification of mystery and novelty, the higher the degrees of excitement by the respondent. There is also a strong correlation between higher levels of polysemy and ratings of arousal, exciting and stimulation. The aesthetic evaluation (beauty) of the building depends and is influenced mainly by the preference of pleasure and admiration, and these three variables are affected by other variables such as ambiguity, complexity, and order. The aesthetic response is a complex process where each variable is affected by another variable, which ultimately leads to a comprehensive aesthetic evaluation.